A comparative Study of Sinhalese Literature In The Eleventh and Twelth Centuries - Dammapala, Gatare (My University, 2016)
Attached

The thesis consists of six chapters. The first chapter deals with the historical background of the period (eleventh and twelfth centuries A.D.) It sums up the results of the Cōla invasion and examines the nature and the functions of intellectual awakening after the re-establishment of Sinhalese rule with special reference to the age of Parākramab āhu I. The second chapter treats briefly almost all the works of the period with their respective authors. It includes various categories of works, literary and otherwise, written in Sinhalese, Pali and Sanskrit. The third chapter concerns the concept of bhakti and its special significance in the context of devotional literature. It also shows how this concept was transferred to the Buddha by later Buddhist devotee writers. The fourth chapter makes a comparative study of the works of Gurulugomi and Vidyācakravarti. It examines their inspirations and influences from such Buddhist works as Avadānas as well as Sanskrit poetic traditions and some Sanskrit prose works. It also assesses the literary quality of each work. The fifth chapter contains a comparative study of the Sasadāvata and the Muvadevdāvata. It deals with the concept of poetry with special reference to the Siyabaslakara, and examines the inspiration of these Sinhalese poems from Buddhist literary traditions in additions to their influence from Sanskrit poetic traditions. It also approaches each work easthetically following the rasa theory as postulated by Ānandavardhana and Visvanātha. The sixth chapter deals with the problem of literary translation. It examines the translating processes put into practice by Ceylonese writers from early times. It pays special attention to the translating processes practiced by Gurulugomi and Vidyācakravarti in their renderings of verse and prose.